2018
DOI: 10.2146/ajhp161035
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic and clinical assessment of kratom

Abstract: Kratom exerts opioid and α-2 receptor agonistic effects as well as antiinflammatory and parasympathetic-impeding effects. Human pharmacologic, pharmacokinetic, and clinical data are of low quality, precluding any firm conclusions regarding safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Other names include Thom, Thang, Kakuam, Ketom, and Biak. Although reports of its use in these indigenous regions date back to the 1800s, it is now being cultivated in other parts of the world [2]. Traditional use involved chewing the fresh leaves or preparing tea from its dried leaves.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other names include Thom, Thang, Kakuam, Ketom, and Biak. Although reports of its use in these indigenous regions date back to the 1800s, it is now being cultivated in other parts of the world [2]. Traditional use involved chewing the fresh leaves or preparing tea from its dried leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Routes of use include inhalation and oral ingestion. Kratom is also added to cocktails, caffeinated beverages, cough syrup, and cannabinoid preparations for recreational use [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Castillo et al (20) reported a case of kratom-induced PRES in a patient on fluoxetine for depression with dextroamphetamine misuse. Kratom exerts α2-adrenoreceptor agonistic effects and is known to induce high blood pressure, particularly when combined with other drugs (68). Mitragynine, the major indole-based alkaloid of kratom, is extensively metabolized by hepatic cytochrome P450 (CYP) isoform 3A4 and 2D6 (69).…”
Section: Multiple Risk Factors In Substance Abuse Patientsmentioning
confidence: 99%